2013
DOI: 10.1021/cs4002282
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Emulsions Based on Supramolecular Hydrogels: Application to Higher Olefins’ Hydroformylation

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…In the presence of an organic phase, the nanocrystallites' adsorption at the water-oil interface resulted in Pickering-like emulsions (Figure 7). For example, the catalytic performance in Rh-catalyzed HF of 1-decene in the sol phase was significantly improved in the presence of α-CD/PEG nanocrystallites (PEG molecular weights of 20,000 g·mol −1 (PEG20000) or 35,000 g·mol −1 (PEG35000)) [31]. As observed previously, an interface saturation occurred over time.…”
Section: Cd-based Pickering-like Emulsionssupporting
confidence: 60%
“…In the presence of an organic phase, the nanocrystallites' adsorption at the water-oil interface resulted in Pickering-like emulsions (Figure 7). For example, the catalytic performance in Rh-catalyzed HF of 1-decene in the sol phase was significantly improved in the presence of α-CD/PEG nanocrystallites (PEG molecular weights of 20,000 g·mol −1 (PEG20000) or 35,000 g·mol −1 (PEG35000)) [31]. As observed previously, an interface saturation occurred over time.…”
Section: Cd-based Pickering-like Emulsionssupporting
confidence: 60%
“…We also showed that hydrogels consisting of poly(ethylene glycol) (PEG20000) and α‐cyclodextrin (α‐CD, cyclic oligomer consisting of six glucopyranose units bridged through 1,4‐glycosidic bonds) helped convert hydrophobic substrates under aqueous biphasic conditions via the formation of a Pickering emulsion (emulsion stabilized by solid particles, α‐CD/PEG crystallites in the present case) . However, the interface between the hydrogel and the organic phase was saturated with time as the Pickering emulsion became too stable.…”
Section: From the 80s To Nowadaysmentioning
confidence: 99%
“…These two locations shouldl ead to different reactiono utcomes because at the oil-water interface the asymmetry,a cidity/basicity,h ydrogen-bonding, and chemical microenvironment are significantly differentf rom those within the bulk water, [33][34][35][36][37][38] which may alter the reaction nature includinga ctivation energy,r eaction rate, and selectivity.I np articular,t he interfacea symmetry in space and polarity may influence the orientation of reactant molecules, likely leading to high selectivity.T he larger oilwater interface area resultsi nt he highers electivity.T his is why the selectivity in the Pickering system is higher than that in . Although Pickeringe mulsion catalysis reactions have been intensively investigated, [39][40][41][42][43][44][45][46][47][48][49][50][51][52] this is the first example showing that the stereoselectivity is enhanced at the oil-water interface, which is furtherenhanced by the continuous flow. ChemSusChem 2017ChemSusChem , 10,1989ChemSusChem -1995 www.chemsuschem.org 2017 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim conventional biphasic systems( 50.3 vs. 34.8 %f or isopulegol, Figure 3).…”
Section: Resultsmentioning
confidence: 97%